The Role of Reversible Protein Phosphorylation in Regulation of the Mitochondrial Electron Transport System During Hypoxia and Reoxygenation Stress in Marine Bivalves - Falfushynska, Halina I.; Sokolov, Eugene; Piontkivska, Helen; Sokolova, Inna M. (Frontiers in Marine Science, 2020)
Fluctuations in the ambient oxygen concentrations represent a major stressor for aerobic organisms causing ATP deficiency during hypoxia and excessive production of reactive oxygen species during reoxygenation. Modulation of the mitochondrial electron transport system activity was proposed as a major mechanism involved in both the mitochondrial injury and adaptive response, but the mechanisms of ETS regulation during hypoxia/reoxygenation (H/R) stress remain poorly understood in hypoxia-tolerant organisms. To address this gap, we focused on the effects of H/R on activities of the mitochondrial Complexes I and IV in hypoxia-tolerant marine bivalves, the blue mussel Mytilus edulis, the Arctic quahog Arctica islandica and the Pacific oyster Crassostrea gigas, exposing them for one or six days to extreme hypoxia (<0.1% O2) followed by one hour of reoxygenation. We used a combination of bioinformatics analysis, biochemical and molecular studies to examine the potential role of the reversible protein phosphorylation in regulation of the Complex I and IV activities and in the mitochondrial responses to H/R stress. Our results showed a strong species-specific modulation of two important kinases, the serine/threonine protein kinase A (PKA) and protein kinase C (PKC) by H/R stress in the studied bivalves. The mitochondrial Complexes I and IV emerged as important targets for modulation by H/R stress, mediated in part through reversible phosphorylation by PKA and PKC. The effects of the reversible phosphorylation on the enzyme activities were species- and condition-specific. In mussels and quahogs, phosphorylation by PKA and PKC led to a strong increase in activity of Complexes I and IV. In oysters, Complexes I and IV were insensitive to PKA and PKC activation except after prolonged hypoxia and reoxygenation when elevated sensitivity to PKA and PKC activation indicated a change in the configuration and/or isoform composition of these enzymes. Non-site-specific dephosphorylation strongly suppressed the activity of Complex I and IV in all three studied species. Because in mammals PKA and PKC can have either damaging or protective effects depending on the timing of activation, our findings underscore the need to further study the physiological implications of H/R-induced modulation of the PKA and PKC activity in hypoxia-tolerant organisms.